The British Labour Government and the development of Chevaline, 1974–79 - Kris Stoddart (Cold War History, 2010)
Between 1974 and 1979 the British Labour Government, led first by Harold Wilson and then by James Callaghan, developed a programme of improvements to the British Polaris Submarine Launched Ballistic Missile (SLBM) system initiated during Wilson's first government between 1964 and 1970. This Polaris improvement programme was known from 1974 onwards as Chevaline. Chevaline offered Britain an indigenous solution to meet the ‘Moscow Criterion’ – the requirement that British strategic missiles had to be capable of penetrating Moscow's ‘Galosh’ Anti-Ballistic missile defence system (ABM) even in the absence of US support. This came during a time of economic austerity in a changing strategic environment which led Labour to explore nuclear cooperation with the French. It also led to calls from within the party to renounce nuclear weapons through unilateral disarmament. This article will shed fresh light on the bitter internal debates that ensued and how a select band of senior ministers responded to this dilemma.